2015
DOI: 10.4103/0972-5229.154548
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous pressure as a reliable predictor for monitoring central venous pressure in patients with burns

Abstract: Background:Optimizing cardiovascular function to ensure adequate tissue oxygen delivery is a key objective in the care of critically ill patients with burns. Hemodynamic monitoring may be necessary to optimize resuscitation in serious burn patients with reasonable safety. Invasive central venous pressure (CVP) monitoring has become the corner stone of hemodynamic monitoring in patients with burns but is associated with inherent risks and technical difficulties. Previous studies on perioperative patients have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The mean difference between the measurements varied from 2.72 (CI 2.1 to 3.3) to 2.92(CI 2.3 to 3.45) which were statistically significant. [12][13][14] .…”
Section: Resultsmentioning
confidence: 99%
“…The mean difference between the measurements varied from 2.72 (CI 2.1 to 3.3) to 2.92(CI 2.3 to 3.45) which were statistically significant. [12][13][14] .…”
Section: Resultsmentioning
confidence: 99%
“…The present study[ 2 ] describes a simple, inexpensive, and minimally invasive technique that can be used as a substitute to CVP and demonstrates the acceptable accuracy of PVP monitoring (the changes in CVP and PVP are strongly correlated and consistent over time). Considering that the clinical utility of CVP as a guide to diagnosis or therapy in critically ill patients continuous to be disputed; also considering the fact that PVP provides equivalent physiological information to CVP,[ 7 8 ] the clinical usefulness of PVP monitoring is questionable.…”
mentioning
confidence: 97%
“…The present study evaluated the use of peripheral venous pressure (PVP) monitoring and demonstrated reliable agreement between central venous pressure (CVP) and PVP over a 10 h period, suggesting that PVP monitoring can be used as a simple, cost-effective, and less invasive substitute for CVP monitoring in patients admitted to the burns Intensive Care Unit. [ 2 ] This method may have potential implications for clinical situations where CVP is used for patient care decisions, in situations where central venous site is inaccessible and also to avoid the complications of central venous catheterization in critically ill burns patients.…”
mentioning
confidence: 99%
“…Анализ волны при измерении периферического венозного давления с помощью стандартного внутривенного катетера может обеспечить недорогой, минимально инвазивный мониторинг у паци-ентов с интраоперационной кровопотерей. Анализ волны при измерении периферического венозного давления продемонстрировал большую чувствительность для обнаружения ранней гиповолемии (всего лишь при 6% кровопотери от ОЦК) по сравнению со стандартным мониторингом [60][61][62]. В акушерстве не проводились исследования, анализирующие периферическое венозное давление при ПРК.…”
unclassified